Theory or philosophy of law? - Woleński, Jan (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The article discusses the theory of law in terms of the extent to which it is part of jurisprudence, on the one hand, and a philosophical pursuit, on the other. The question is explored considering the historical development of the legal sciences and the situation of Polish theory of law in the latter half of the twentieth century. Also, the author relies on the analysis of selected theoreticallegal concepts, notably the so-called multiplane theory of law and the views thought of Zygmunt Ziembiński. The conclusions suggest that philosophy is inevitable in jurisprudence.